2013
DOI: 10.1189/jlb.1012520
|View full text |Cite
|
Sign up to set email alerts
|

MGL signaling augments TLR2-mediated responses for enhanced IL-10 and TNF-α secretion

Abstract: DCs orchestrate immune responses to infectious pathogens and disturbances in tissue integrity. Equipped with C-type lectins, DCs can respond to environmental changes in glycosylation. Many C-type lectins are capable of modulating TLR activation, thereby facilitating tailor-made immune reactions. Here, we investigated the signaling properties of the C-type lectin MGL and show that MGL engagement by agonistic antibodies or carbohydrate ligands couples to TLR signal transduction for increased IL-10 and TNF-α secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
111
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(127 citation statements)
references
References 46 publications
12
111
0
Order By: Relevance
“…Recently, the capacity of MGL to modulate TLR-2 signaling has been reported 51. In accordance with this, we showed that upon in vitro T. cruzi infection, mMGL-/- Mφ displayed significantly less expression of MHC-II and TLR-4.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, the capacity of MGL to modulate TLR-2 signaling has been reported 51. In accordance with this, we showed that upon in vitro T. cruzi infection, mMGL-/- Mφ displayed significantly less expression of MHC-II and TLR-4.…”
Section: Discussionsupporting
confidence: 89%
“…Some of these studies suggest that MGL improves DC antigen presentation and triggers distinct signaling pathways that regulate APC functions through the expression of specific molecules and cytokines that modulate the innate and adaptive immune response 24, 51. This hypothesis has been driven by the knowledge that MGL works as a molecular target for Gal/GalNAc or Tn-carrying tumor-associated antigens on DCs 24, 25, 52 and is supported by subsequent data showing that mMGL recognizes Gal/GlalNAc residues carried by glycoproteins and/or glycosphingolipids present on the helminth Schistosoma mansoni inducing phagocytosis, endocytosis, enhancing parasite glycopeptide presentation and promoting the polarization to Th2 responses 27, 53.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MR, MGL, or DC-SIGN have also been described to signal upon receptor engagement (17, 48). Both DC-SIGN and MGL triggering modulate TLR signaling to enhance IL-10 production (29, 4850).…”
Section: Discussionmentioning
confidence: 99%
“…Both DC-SIGN and MGL triggering modulate TLR signaling to enhance IL-10 production (29, 4850). Therefore, the simultaneous engagement of multiple CLRs could initiate signaling responses that potentially affect the routing of other CLRs, as we here describe for DCIR and DC-SIGN.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the human mannose receptor contributes to antifungal T H 17 cellmediated immunity 93 , whereas the recognition of different allergens by this mannose receptor results in the down regulation of TLR-induced IL-12p70 expression, thereby favouring T H 2 cell responses 94 . MGL (also known as CLEC10A) engagement enhances TLRinduced IL-10 expression, resulting in the induction of regulatory T cells 95,96 . CLEC9A in mice is involved in the induction of antigen-specific T FH cells 97 ; however, this receptor seems to be more important for antigen cross-presentation than for the production of proinflammatory cytokines 98,99 , suggesting that cooperation between CLEC9A and other receptors might underlie the observed effects on T FH cell responses.…”
Section: Other Clrs In T H Cell Differentiationmentioning
confidence: 99%